(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
We, university teachers, invest most of our time in offering written or oral feedback to the student’s assignments. However, one of the issues is to know what students do with these comments. Do they follow them? Do they omit them? The aim of this research is to present the results of the analysis carried out about the actions that students perform based on 434 written comments provided by 2 supervisors teachers in total of 2 drafts produced in the development of the final undergraduate research. To analyze the actions carried out by the writers from the feedback received, Faigley and Witte (1981) taxonomy was adapted. These actions were analyzed in terms of adoption (addition, substitution, permutation, consolidation and elimination), non adoption or suppression of the suggestions offered to improve the text. The results show that students adopt almost all the suggestions offered. Basically, what they do the most is to consolidate and substitute. Likewise, it is possible to report that there is a relation between the way comments are offered and the actions the writers carry out. While, this is a case study, it is interesting to notice a certain relation between offering order and the text addition and questions with the text modifications.